The desmosomal cadherin Desmoglein-2 controls extracellular matrix expression and remodeling via NF-κB signaling in keratinocytes - Hunter, Sadie E.; Patel, Zara T.; Mateo, Beatriz; Powers, Joshua M.; Shull, Austin Y.; Dubash, Adi D. (Frontiers in Cell and Developmental Biology, 2025)
Desmogleins are transmembrane cadherin proteins and obligate members of the desmosome, a cell-cell adhesion complex which connects adjacent cells and provides structural integrity to tissues. While Desmogleins are well-known for their importance in maintenance of cell-cell junctions, several studies have also highlighted their role in signaling crosstalk with cell-matrix adhesions and the extracellular matrix (ECM). We have recently shown that Desmoglein-2 (Dsg2) controls cell spreading on ECM substrates (fibronectin and collagen) and phosphorylation of focal adhesion proteins via Rap1 GTPase signaling. In our current study, we show that loss of Dsg2 in keratinocytes enhances the expression of ECM proteins and matrix metalloproteinases (MMPs), an effect that was not recapitulated upon loss of Desmocollin-2 (Dsc2) or loss of Dsg2 in other epithelial cell types. Signaling pathways well-known to control ECM function (TGF-β and Rho) were not involved in Dsg2-mediated changes in ECM gene expression, but an analysis of global transcriptome changes by RNA sequencing identified major changes in Nuclear Factor-kappa B (NF-κB)-mediated signaling in Dsg2-deficient cells. Interestingly, NF-κB (RelA) activation is elevated in Dsg2-deficient cells, and knockdown of RelA rescued both the enhanced expression of ECM/MMP genes and the enhanced migratory ability of Dsg2-deficient cells. Taken together, this study has identified an important link between Dsg2 and NF-κB signaling involved in controlling matrix production and remodeling, which has relevance for multiple processes in the epidermis such as wound healing and psoriasis.